A highly potent small-molecule antagonist of exportin-1 selectively eliminates CD44+CD24- enriched breast cancer stem-like cells. (January 2023) - Liu, Caigang; Zhang, Yixiao; Gao, Jiujiao; Zhang, Qi; Sun, Lisha; Ma, Qingtian; Qiao, Xinbo; Li, Xinnan; Liu, Jinchi; Bu, Jiawen; Zhang, Zhan; Han, Ling; et al.
Abstract: Breast cancer stem-like cells (BCSCs) have been suggested as the underlying cause of tumor recurrence, metastasis and drug resistance in triple-negative breast cancer (TNBC). Here, we report the discovery and biological evaluation of a highly potent small-molecule antagonist of exportin-1, LFS-1107. We ascertained that exportin-1 (also named as CRM1) is a main cellular target of LFS-1107 by nuclear export functional assay, bio-layer interferometry binding assay and C528S mutant cell line. We found that LFS-1107 significantly inhibited TNBC tumor cells at low-range nanomolar concentration and LFS-1107 can selectively eliminate CD44 + CD24 - enriched BCSCs. We demonstrated that LFS-1107 can induce the nuclear retention of Survivin and consequent strong suppression of STAT3 transactivation abilities and the expression of downstream stemness regulators. Administration of LFS-1107 can strongly inhibit tumor growth in mouse xenograft model and eradicate BCSCs in residual tumor tissues. Moreover, LFS-1107 can significantly ablate the patient-derived tumor organoids (PDTOs) of TNBC as compared to a few approved cancer drugs. Lastly, we revealed that LFS-1107 can enhance the killing effects of chemotherapy drugs and downregulate multidrug resistance related protein targets. These new findings provide preclinical evidence of defining LFS-1107 as a promising therapeutic agent to deplete BCSCs for the treatment of TNBC.